2011
DOI: 10.4103/0972-124x.85662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sonic and ionic toothbrush in reduction in plaque and gingivitis

Abstract: Background:A paucity of conclusive research exists on the optimal design and mode of action of toothbrushes, leading to the introduction of new generation of toothbrushes. Sonic and ionic toothbrushes belong to this new generation of toothbrushes. The aim of the present study was to clinically assess and compare the efficacy of the sonic and ionic toothbrushes.Materials and Methods:A single blind study, using a split-mouth method, was conducted for 45 days on a total of 22 (11 males and 11 females) student vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…To date, many studies have reported on various dental hygiene products other than manual toothbrushes, such as high-pressure oral spray devices 16) , sonic electric toothbrushes 17) , and essential oil mouth rinses 18) . However, no study has been conducted on chewable toothbrush use in general adults.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have reported on various dental hygiene products other than manual toothbrushes, such as high-pressure oral spray devices 16) , sonic electric toothbrushes 17) , and essential oil mouth rinses 18) . However, no study has been conducted on chewable toothbrush use in general adults.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this revealed that ionic powered toothbrushes had significantly better outcomes compared with the manual ones in reducing plaque, especially at molar sites, in a single use. A previous study 13 compared the efficacy of sonic and ionic toothbrushes, and then, the sonic toothbrushes were superior to the manual ionic ones although no significant difference could be observed between two groups. In this randomized clinical study, a newly developed powered ionic device was used to improve the power and frequency.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies suggest that an ionic toothbrush is more effective in plaque removal than a negative ionic toothbrush 7–9 . On the contrary, a few studies show that ionic toothbrushes were different from conventional toothbrushes, 10 especially in terms of a reduction in Gingival Index 11–13 . There is a need to develop ionic toothbrushes capable of efficiently and effectively removing dental plaque.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have reported about various dental hygiene product other than manual toothbrushes, such as high-pressure oral spray devices,[ 1 ] sonic electric toothbrushes,[ 14 ] and essential oil mouth rinses. [ 15 ] However, very few studies have been conducted on the use of chewable toothbrushes in children.…”
Section: Discussionmentioning
confidence: 99%